Chemically Cross-linked Hydrogels Based on Cellulose Nanofibril for Oral Drug Delivery - Lopes, Francielle; Pitlovanciv, Luis Gustavo; Kerek , André Luis; Garcia, Jarem Raul; Fiorin, Barbara Celânia; Lima-Tenório, Michele Karoline; Gonçalves Viana, Adriano (Orbital: The Electronic Journal of Chemistry, 2025)
Nanocellulose-based hydrogels have emerged as promising platforms for drug delivery in the gastrointestinal environment due to their biocompatible and biodegradable properties, aligning with the 3, 9, and 12 Sustainable Development Goals (SDG). In this study, we investigated the modification of cellulose nanofibrils (CNF) with glycidyl methacrylate and the subsequent synthesis of chemical hydrogels containing N',N'-dimethylacrylamide (DMA), and sodium acrylate (NaAac). The structural and morphological characterization of the hydrogels was carried out using techniques such as FTIR (Fourier-transform infrared spectroscopy), 1H NMR (proton Nuclear magnetic resonance), and SEM (scanning electron microscopy). The fluid absorption capacity and swelling kinetics were evaluated, as well as the contribution of swelling mechanisms to these processes. Among the formulations developed, H2 (50 mg of CNF, 50 mg of DMA, 50 mg of NaAac) was demonstrated to be responsive to changes in pH and ionic strength, which can potentially generate a material capable of acting as a carrier for controlled drug release systems in the gastrointestinal environment. This study suggests that modified CNF hydrogels have potential applications as a controlled release device in the gastrointestinal environment and contribute to achieving the SDG, offering a strategy to improve therapeutic efficacy, reduce side effects, and promote responsible consumption and production practices.